2018
DOI: 10.1071/py17178
|View full text |Cite
|
Sign up to set email alerts
|

Homeless adults' access to dental services and strategies to improve their oral health: a systematic literature review

Abstract: Homeless people have poor oral health and high treatment needs, yet tend to make problem-based dental visits. This review aimed to determine how and where homeless adults receive oral health care, the barriers that prevent homeless adults accessing dental care and find strategies to promote oral health to homeless adults. The databases MEDLINE via OvidSP, PubMed, CINAHL and Scopus were searched using the keywords: homeless, roofless, houseless, rough sleeper, couch surfer, shelter, hostel, dental and oral heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 31 publications
4
31
0
4
Order By: Relevance
“…However, that review only focused on the characteristics of the population acting as barriers to care and thus bias towards the structural components of access could have been introduced. A recent systematic review which included studies published in developed countries identified similar population and system level factors affecting homeless people's access to dental care . Lack of inclusion of grey literature appears to explain why some elements captured in our review were not identified in others (ie, confusion on how benefit eligibility affects right to care and language difficulties acting as barriers to care; support to register and attend services as an enabler).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, that review only focused on the characteristics of the population acting as barriers to care and thus bias towards the structural components of access could have been introduced. A recent systematic review which included studies published in developed countries identified similar population and system level factors affecting homeless people's access to dental care . Lack of inclusion of grey literature appears to explain why some elements captured in our review were not identified in others (ie, confusion on how benefit eligibility affects right to care and language difficulties acting as barriers to care; support to register and attend services as an enabler).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review which included studies published in developed countries identified similar population and system level factors affecting homeless people's access to dental care. 55 Lack of inclusion of grey literature appears to explain why some elements captured in our review were not identified in others 55 (ie, confusion on how benefit eligibility affects right to care and language difficulties acting as barriers to care; support to register and attend services as an enabler). Peer advocates can be an important source of support for people experiencing homelessness to register and attend services.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Individuals who are homeless (those without a fixed, regular, and adequate night-time residence) had higher mortality rates and experience the dual burdens of DPs, CDs compared to the general population [4,5,14] due to structural and system-level barriers (e.g., lack of affordable housing, shrinking safety nets, health care systems models, health services affordability, lack of accessibility to health and social services) [15][16][17][18][19], social exclusion [18]. People experiencing homelessness frequently suffer serious mental disorders (e.g., psychotic disorders, mood and personality disorders, substance and alcohol use disorders) [20,21] and modifiable risk factors (e.g., diet, smoking) [22,23], which also contribute to poor health profiles and premature mortality [5,21].…”
Section: Introductionmentioning
confidence: 99%